Pemerolehan Bunyi-bunyi Bahasa Anak Usia 2 Tahun (Contoh Kasus pada Ghania) - Savitri Eka Wardani; Houtman Houtman (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
Exploration of phonemes for toddlers is a miracle process that occurs for humans. Its uniqueness raises curiosity about the stages it goes through. In this study, by selecting the subject of the study a toddler named Ghania, obtained results that show the process of forming language sounds with characteristics that basically have general characteristics that occur in humans. By using a qualitative approach and analysis of the observations made, it is found that the process of acquiring the sounds of the Ghanaian language has a tendency to optimize vowel phonemes and attach them to the morphological unit of words meaning Action.